2017
DOI: 10.1186/s13075-017-1266-4
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognostic factors guiding treatment decisions in rheumatoid arthritis patients: a review of data from randomized clinical trials and cohort studies

Abstract: Prognostic factors are used for treatment decisions in rheumatoid arthritis (RA). High disease activity, the early presence of erosions, and autoantibody positivity are the most frequently used poor prognostic factors but other features, such as functional disability, extraarticular disease, or multibiomarkers, are also assessed. Prognostic factors are incorporated in current treatment recommendations for the management of RA and are used as inclusion criteria in randomized controlled trials. They are defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 47 publications
2
49
0
2
Order By: Relevance
“…Coixol, Coixenolide, Myristic acid Anti-inflammation Anti-oxidant effects Anti-tumour activities (Seo et al, 2000) Name Ingredients Percentage (%) Function only (Albrecht and Zink, 2017). Hence, the association between a lower IS risk and receiving the CHP treatment in combination with WM among severe RA patients was not significant.…”
Section: Discussionmentioning
confidence: 94%
“…Coixol, Coixenolide, Myristic acid Anti-inflammation Anti-oxidant effects Anti-tumour activities (Seo et al, 2000) Name Ingredients Percentage (%) Function only (Albrecht and Zink, 2017). Hence, the association between a lower IS risk and receiving the CHP treatment in combination with WM among severe RA patients was not significant.…”
Section: Discussionmentioning
confidence: 94%
“…The long-term use of PSL potentially has multiple adverse effects, and its use is usually limited to refractory patients with high disease activity according to clinical recommendations [3]. Previous studies have also reported that high titers of RF or anti-CCP antibody are poor prognostic factors [33], and that greater age and female sex are independently associated with the increased ESR levels in RA patients [34]. Furthermore, eGFR levels are…”
Section: Discussionmentioning
confidence: 99%
“…Corrona is a US registry, and it is possible that the results may differ in other countries 13 and international registries. Additionally, this study focused on only a subset of PPF, because there is not a widely accepted consensus definition 14 . The definitions of PPF in RA differ by region and therefore the introduction of further confounding is a possibility.…”
Section: Discussionmentioning
confidence: 99%